Current State and Progress of Research on the Role of lncRNA in HBV-Related Liver Cancer - Wang, Xueke; Kang, Meisong; Liu, Chun; Lin, Ting; Han, Xiao; Jiang, Xiwen (Frontiers in Cellular and Infection Microbiology, 2021)
Hepatocellular carcinoma (HCC) is a malignant tumor with the highest mortality rate in the world, and hepatitis B virus (HBV) plays an important role in its development. Long noncoding RNA (lncRNA) is highly related to the inactivation of tumor suppressor genes and the activation of oncogenes in HCC. Researchers have used high-throughput sequencing technology to identify many noncoding transcripts related to the development of HCC and have studied the interaction between these transcripts and DNA, RNA, or protein to determine the relevant mechanism in the development of HCC. In general, the research on lncRNA represents a new field of cancer research, and the imbalance in lncRNA plays an pivotal role in the occurrence of liver cancer. In this review, we summarize some of the dysfunctional lncRNAs in human HCC associated with HBV infection. Their regulatory pathways, functions, and potential molecular mechanisms in the occurrence and development of HCC are discussed.